PROGRAM LAYANAN TAMAN BACAAN MASYARAKAT RUMAH KREATIF WADAS KELIR - Hafidz, Nur; Nurul Hidayat, Fariz; Nurbaiti, Amalia (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2024)
Rumah Kreatif Wadas Kelir Community Reading Park Service Program is a literacy empowerment initiative that focuses on developing reading interest and creativity of the community, especially among children, adolescents, and the elderly. This Program was held in Karangklesem Village, South Purwokerto, Jalan Wadas Kelir as an effort to provide access to quality reading materials and creative activities that support learning outside of formal schools. This research method uses descriptive qualitative with Case Study approach collected through participatory observation, interviews with TBM managers, and documentation. The results showed that the Reading Garden Community Service Program Wadas Kelir Creative House through four services, namely lending and borrowing services, children's creativity Development Services, learning facilities services, and tutoring services. This Program is expected to improve the quality of literacy, build positive character, and open opportunities for the community to actively participate in social and cultural development. From here, the process of community participation and sustainability of activities, the TBM service program plays an important role in strengthening the literacy ecosystem at the local level with long-term impacts on the surrounding community